PSYCHOLOGICAL INTERVENTIONS FOR PREGNANT WOMEN EXPERIENCING INTRAUTERINE FETAL DEATH (IUFD): A SCOPING REVIEW - Restuning Widiasih; Ermiati Ermiati; Amiranendya Shabrina Yudiaputri; Fairuz Amelinda Rahmat; Finny F. H.; Nurul Sopia; Riska Nur Assyifa Febrianti; Glorianita A. R. Araujo (Journal of Maternity Care and Reproductive Health, 2026)
Pregnancy is a sensitive period that may predispose women to emotional and psychological changes. The loss of a fetus in utero, known as Intrauterine Fetal Death (IUFD), can result in severe psychological consequences, including grief, stress, and depression. However, research examining psychological interventions for women experiencing IUFD remains limited. This study aims to provide an overview of psychological interventions for mothers who experience Intrauterine Fetal Death (IUFD). This review employed a scoping review approach using three databases: PubMed, EBSCO, and ScienceDirect. The article selection process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The search keywords included pregnancy or gestation, fetal death, IUFD, stillbirth, psychology, and nursing interventions. The inclusion criteria included peer-reviewed journals, English language publication, and RCT or Quasi-experimental studies. Based on the screening and eligibility process, seven articles met the inclusion criteria. The findings indicate that structured therapeutic approaches such as mind body group therapy, yoga, and art therapy are effective in reducing symptoms of depression and stress, while also enhancing self-acceptance and quality of life. Future research is recommended to integrate psychological, social, and spiritual approaches into nursing practice to support the emotional well-being of mothers following fetal loss.